Effect of electrical discharge machining process parameter on surface topograhy - Lee, Wai Loon (2010)
This paper was developed the mathematical modelling of EDM process parameters to predict the surface roughness of Ti-6Al-4V. The process is used in situations where intricate complex shapes need to be machined in very hard materials such as titanium alloy. However, the process generates surfaces that have poor properties such as high surface roughness, slow machining removal rate and moderate electrode wear rate. These properties vary with different levels of the main process parameters such as peak current, servo voltage, pulse on-time and pulse off-time. The aim of this paper is to perform experimental work that has been done in order to explore the relationships between input and output parameters. Response surface design is used because the input and output parameter were suspect have curvature relationships. A mathematical model develops base on response surface method. The significant coefficients were obtained by performing Analysis of Variance (ANOVA) at 95% level of significance. Adequacy test was carried out to check the fitting of the models. It found that the peak current, servo voltage and pulse on time are significant in material removal rate and surface roughness. Peak current has the greater impact on surface roughness and material removal rate. Finally, a metallurgical microscope is carried to observe the surface topography.